MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN DESAIN KECANTIKAN KOMPETENSI KEAHLIAN TATA KECANTIKAN RAMBUT DI SMKNEGERI 3 PEKANBARU - Dewi Afriani S, Dina Ranap; Rostamailis, Rostamailis; Yusmerita, Yusmerita (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2013)
This study aims toreveal, the motivation to learnthesubjectDesignBeautyHairBeautySkills CompetencystudentsinSMKNegeri 3Pekanbaruwhichincludesindicator(1) The desireand thedesire ofthe subjectssucceededinBeautyDesign(2) Encouragementandlearningneedsin theBeautyDesign(3 )expectationsandfutureaspirationsin learningDesignBeauty. This type of researchisdescriptivequantitative. Populationandsampleanentirestudentcompetency skillsHair BeautyClassesXandXIof the school year2010/2011SMKNegeri 3Pekanbaru, amounting to 65people. Collecting datathroughquestionnaires.Data analysis techniquesin the form ofdescriptivestatisticswiththe level oftechnicalattainmentpercentageof respondentswithformula.Results showedthat thelearning motivationbypassionand the desireto succeed inlearningBeautyDesignby64.44% with thelow category, encouragementandlearningneedsinBeautyDesigncategoryat61.69% withlowandhopesandaspirationsof the future inBeautyDesignamounted to74.27% with themedium category Â Kata Kunci :Hasrat dan Keinginan Berhasil, dorongan dan Kebutuhan dalam Belajar, Adanya Harapan akan Citaâ€“cita Masa Depan